A resident-led clinic that promotes the health of refugee women through advocacy and partnership - Stairs, Jocelyn; Bal, Navpreet; Maguire, Finlay; Scott, Heather (Canadian Medical Education Journal, 2019)
Implication Statement Longitudinal global health experiences promote cultural competency and a commitment to caring for underserved populations beyond residency. This paper describes a longitudinal, co-curricular local global health experience. Obstetrics and gynaecology residents have partnered with the Family Medicine-led Halifax Newcomer Health Clinic to provide education and clinical well woman care to refugee women. This resident-led initiative meets the care needs of an underserved population while promoting resident engagement in health advocacy.